Worker Knowledge of Pension Provisions - Mitchell, Olivia S. (Journal of Labor Economics, 1988)
This article evaluates the quality of workers' information regarding pension offerings using both administrative records and worker reports of pension provisions. Missing and incorrect information is wide-spread. Unionized employees, higher income workers, better educated workers, and those with seniority are better informed about their pensions. There are also demographic differences: minorities have less pension knowledge than whites, but women are better informed than men along several pension dimensions. Myopia about pension incentive structures is troubling since workers may save or consume suboptimally, change jobs, or retire earlier than they would have if equipped with better pension information.